2022
DOI: 10.3390/cells11152417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Collagen Crosslinkers on Dentin Bond Strength of Adhesive Systems: A Systematic Review and Meta-Analysis

Abstract: This study aimed to identify the role of crosslinking agents in the resin–dentin bond strength (BS) when used as modifiers in adhesives or pretreatments to the dentin surface through a systematic review and meta-analysis. This paper was conducted according to the directions of the PRISMA 2020 statement. The research question of this review was: “Would the use of crosslinkers agents improve the BS of resin-based materials to dentin?” The literature search was conducted in the following databases: Embase, PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 155 publications
1
14
0
1
Order By: Relevance
“…In addition, although the bonding strength of all groups decreased after 10,000 thermocycling, the EDC-treated samples (EDCw, EDCw + EWB, and EDCe) maintained higher bonding strengths compared with the control group, which is consistent with the results of other studies ( Hardan et al, 2022 ; Maravic et al, 2021 ; Mazzoni et al, 2018 ). The reason is speculated to be that covalent cross-links produced with EDC inactivate the active sites of dentin matrix metalloproteinases ( Maravic et al, 2021 ; Tjaderhane, 2015 ), causing EDC-treated samples to undergo less hydrolysis and enzymatic hydrolysis, and maintain the integrity of the hybrid layer to a greater extent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, although the bonding strength of all groups decreased after 10,000 thermocycling, the EDC-treated samples (EDCw, EDCw + EWB, and EDCe) maintained higher bonding strengths compared with the control group, which is consistent with the results of other studies ( Hardan et al, 2022 ; Maravic et al, 2021 ; Mazzoni et al, 2018 ). The reason is speculated to be that covalent cross-links produced with EDC inactivate the active sites of dentin matrix metalloproteinases ( Maravic et al, 2021 ; Tjaderhane, 2015 ), causing EDC-treated samples to undergo less hydrolysis and enzymatic hydrolysis, and maintain the integrity of the hybrid layer to a greater extent.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies that pretreated demineralized dentin with 0.3M EDC in water for 1 min have demonstrated the improved bonding strength of the resin–dentin interface ( Comba et al, 2019 ; Hardan et al, 2022 ; Maravic et al, 2021 ; Mazzoni et al, 2013 ; Mazzoni et al, 2014 ). However, studies have shown that nearly half of the demineralized dentin the adhesive should infiltrate is still infiltrated by residual water during the process of dentin bonding ( Tjaderhane et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, these cross-linked collagen matrices also possess antibacterial and anti-biofilm activities (Daood et al, 2018;Fonseca et al, 2019) The incorporation of chitosan into dentin adhesives increases long-term bond strength and creates an interface with antibacterial properties (Elsaka and Elnaghy, 2012;Diolosà et al, 2014) The usage of the chitosan-riboflavin combination enhanced the mechanical properties of dentin and synergistically reduced the degradation of the resin-dentin interface (Daood et al, 2018). The study results, in contrast to previous results (Hardan et al, 2022), refute the finding that chitosan is a weak crosslinker and does not have a significant effect when used alone.…”
Section: Effect Of the Different Types Of Cross-linkersmentioning
confidence: 75%
“…This hybrid-layer degradation is caused by enzymes from the zymogen protease family in the extracellular matrix, specifically matrix metalloproteinases (MMPs) and cysteine cathepsins (CCs). These enzymes are activated in an acidic environment, such as acid-etching conditioning (phosphoric acid) or adhesive itself [ 25 ]. Pretreatment with chlorhexidine after acid conditioning can reduce the activity of the zymogen protease family.…”
Section: Discussionmentioning
confidence: 99%